(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The study reconstructs the fortune of Dido abandoned by Pietro Metastasio from the first two decades of the eighteenth century to the first decades of the nineteenth century, in a time span of nearly a hundred years. In that period of time, historical and major political changes have affected the city of Lombardy, as well as musical taste changes, they see the emergence of italian primedonne on the vocal scene and increasing the orchestra. However, the structural flexibility of this libretto and the new elements it contained, in essence, consented to the codes of representation of creep in the voids of the dramatic text, rearranging the horizon of expectation of the audience in an ever new and present form.